Religion, politics and Symbolic Performance: An Analysis Of The Work Of Archbishop Desmond Tutu From July 1989 To February 1990 - TAYLOR_DW (Department of Religious Studies, 2024)
This document follows the performances of Desmond Tutu, the Archbishop of Cape Town, from the international release of theological statement until the release of South African political prisoner, Nelson Mandela. The leadership of the Archbishop is analysed using the broad methodological framework of "Dramatism" as established by literary critic, Kenneth Burke. Burke's work is then expanded to incorporate performance theory as ~el1 as post-Burkian criticism to examine the range of impact of the leader of an oppositional culture in an established time period of social change. The dynamics of cultural conflict and social action are defined in terms of symbolic performance. Burke's "Dramatist" methodology is based upon a "comic" attitude of history d~e to the mistaken nature of the ruling class. Within this attitude, historical interpretation and symbolic direction are controlled and focused through a "comedic master". Tutu fulfills this role by being the central ''performer" that articulates the South African oppositional struggle through the world media network. As i i the focus of international press coverage, the Archbishop serves as the lens by which criticism of the dominant ruling culture is expressed. This criticism is based upon his personal theology of liberation set against the oppressive nature of the apartheid legal system that oppresses the black South African population. After the foundations of symbolic performance and leadership are established, special attention is placed upon a chronology of historical action that serves as a catalyst towards social reform in South Africa. Once this is shown, transference of these symbolic actions is established as a form a validation and publicity for similar cultural struggles internationally. Acts of symbolic correction are expressed through the Archbishop's involvement with the campaign for economic sanctions against the oppressive government. Finally, the transition of symbolic leadership is manifested with the release of a greater cultural symbol, found in the character of Nelson Mandela. Tl, i .,_ paper stresses the symbiotic nature of religious motivation and political action through symbolic drama. Using performance theory it is possible to examine the effects of the Archbishop's actions as the "comedic master" of the oppressed culture and the flux of symbolic relationships on the international level.